Axiological ethical values of news on Alerian websites : An analytical study of Al-nahar and Alkhabar electronic sites - Nedjai, Samia; Djefafla, Daoud (Journal of Human Sciences, 2022)
Moral values ​​are the basis on which many media outlets rely in their performance of their functions, which falls under the framework of the so-called social responsibility and value imperative of the media towards individuals in particular and society in general; This is what applies in particular to the traditional media system due to its nature, which enables control over its content. But that may not apply to the electronic press with its new technological and communication specifications, which has imposed a new legal and value reality commensurate with its changing nature. This study sought to highlight the most important changes in The value implications of electronic news, given that the moral values ​​that govern professional practice, society ... etc. are among the most important elements that govern the process of selecting and publishing news.